An Efficient Gram‐Scale Chemical Synthesis of Purine Locked Nucleic Acid Nucleoside‐5′‐O‐Triphosphates. Issue 6 (20th June 2022) - Shanmugasundaram, Muthian; Senthilvelan, Annamalai; Kore, Anilkumar R.
Abstract: This article presents a simple, reliable, straight‐forward, general, and efficient chemical method for the gram‐scale synthesis of purine locked nucleic acid (LNA) nucleotides, such as LNA guanosine‐5′‐ O ‐triphosphate (LNA‐GTP) and LNA adenosine‐5′‐ O ‐triphosphate (LNA‐ATP), starting from the corresponding nucleoside. The reaction pathway employs an improved protection‐free "one‐pot, three‐step" Ludwig synthetic strategy. The first step involves monophosphorylation of nucleoside with phosphorus oxychloride followed by reaction with tributylammonium pyrophosphate and subsequent hydrolysis of the resulting cyclic intermediate to furnish the corresponding LNA nucleotide in good yields. It is noteworthy that the reaction affords high‐purity (>99.5%) LNA nucleotide after diethylaminoethyl Sepharose column purification. © 2022 Wiley Periodicals LLC. Basic Protocol : Synthesis of LNA nucleoside‐5′‐ O ‐triphosphates